VD_FINDINFO HC / 2014 / 518 vom 10. Juni 2014 - VD Tribunal cantonal (2014)
TRANSACTION JUDICIAIRE, ERREUR ESSENTIELLE, OBLIGATION D'ENTRETIEN, REVENU, ÉQUITÉ | 133 al. 1 CC, 276 al. 1 CC, 276 al. 2 CC, 285 al. 1 CC, 279 CPC (CH)